Molecular Characterization and Functional Analysis of OsPHY1, a Purple Acid Phosphatase (PAP)–Type Phytase Gene in Rice(Oryza sativaL.) - Rui-juan LI; Wen-jing LU; Cheng-jin GUO; Xiao-juan LI; Jun-tao GU; Kai XIAO (Journal of Integrative Agriculture, 2012)
Abstract: As a specific type of acid phosphatses, phytases play diverse roles in plants by catalazing the degradation of phytic acid and its derivatives. In this study, a rice phytase gene referred to OsPHY1 has been functionally characterized. OsPHY1 contains a 1 620 bp of open reading frame, encoding a 539-aa polypeptide. A conserve domain metallophosphatase (MPP) (MPP_PAPs), generally harbored in phytase and purple acid phosphatases (PAP), was identified in OsPHY1 (residue 194-398). Phylogenetic analysis revealed that OsPHY1 shares high similarities with phytase genes and PAP-type genes that derived from diverse plant species. The OsPHY1 transcripts were detected to be abundant in germinating seeds, suggesting that this gene plays potential roles on degradation of seed phytic acid and its derivatives during the germination process. Biochemical analysis confirmed that OsPHY1 possesses strong catalytic activities on phytic acid-Na2, with optimal temperature of 57°C and suitable pH of 3.5. Based on transgene analysis, the putative role of OsPHY1 in plants on utilization of phytate was assessed. Under the condition that phytic acid-Na2 was used as sole P source, the OsPHY1-overexpressing tobacco plants behaved higher phytase activities, higher concentrations of Pi, more accumulative amount of total phosphorus, and much more improved growth traits than those of the control plants. Therefore, OsPHY1 is acted as an important component on degradation of the phytins during the seed germination process in rice. Also, OsPHY1 has a potential use on generation of elite crop germplasms with improved use efficiencies on phytate and its derivatives.